Dynamic Regulation of Synaptopodin and the Axon Initial Segment in Retinal Ganglion Cells During Postnatal Development - Schlüter, Annabelle; Rossberger, Sabrina; Dannehl, Dominik; Janssen, Jan Maximilian; Vorwald, Silke; Hanne, Janina; Schultz, Christian; Mauceri, Daniela; Engelhardt, Maren (Frontiers in Cellular Neuroscience, 2019)
A key component allowing a neuron to function properly within its dynamic environment is the axon initial segment (AIS), the site of action potential generation. In visual cortex, AIS of pyramidal neurons undergoes periods of activity-dependent structural plasticity during development. However, it remains unknown how AIS morphology is organized during development for downstream cells in the visual pathway (retinal ganglion cells; RGCs) and whether AIS retains the ability to dynamically adjust to changes in network state. Here, we investigated the maturation of AIS in RGCs during mouse retinal development, and tested putative activity-dependent mechanisms by applying visual deprivation with a focus on the AIS-specific cisternal organelle (CO), a presumed Ca2+-store. Whole-mount retinae from wildtype and Thy1-GFP transgenic mice were processed for multi-channel immunofluorescence using antibodies against AIS scaffolding proteins ankyrin-G, βIV-spectrin and the CO marker synaptopodin (synpo). Confocal microscopy in combination with morphometrical analysis of AIS length and position as well as synpo cluster size was performed. Data indicated that a subset of RGC AIS contains synpo clusters and that these show significant dynamic regulation in size during development as well as after visual deprivation. Using super resolution microscopy, we addressed the subcellular localization of synpo in RGC axons. Similar to cortical neurons, RGCs show a periodic distribution of AIS scaffolding proteins. A previously reported scaffold-deficient nanodomain correlating with synpo localization is not evident in all RGC AIS. In summary, our work demonstrates a dynamic regulation of both the AIS and synpo in RGCs during retinal development and after visual deprivation, providing first evidence that the AIS and CO in RGCs can undergo structural plasticity in response to changes in network activity.